Room Temperature Control using Voltage Controller for Miniature Powder Milk Storage - SUTEDJO SUTEDJO; RACHMA PRILIAN EVININGSIH; LUKI SEPTYA MAHENDRA; ENJELS FATKHUR ROHMAN SUYADI (Jurnal Elkomika, 2023)
ABSTRAK